CALCULATION OF THE NUMBER OF STUDENTS APPLICATION ABSENT STMIK JAKARTA STI & K 2007/2008 SEMESTER ATA USING MICROSOFT VISUAL FOXPRO 9.0 - Armita Tri Utami; Linda Wahyu Widianti, Skom, MMSI Linda Wahyu Widianti, Skom, MMSI (Jurnal Sistem Informasi, 2010)
Jakarta STMIK STI & K is a High School which is engaged in computer education,in everyday activities is made up of teaching and learning process called lectures. Inlectures students must complete the activity absences with their respective initials.From the result of absenteeism, we can see the total number of incoming andincoming students. With the making of an application program design calculation ofthe number of absent students, it is expected to be useful for the interests of theabsentee students and can be used properly. This application is built using MicrosoftVisual FoxPro 9.0, because by using Microsoft Visual FoxPro 9.0 applicationprogram calculate the number of absences is to be easily designed by utilizing thevarious facilities provided by Microsoft Visual FoxPro 9.0, so this application easy touse and made with easy to view (the user friendly).